Bridging the Clinic to Community: Music Performance as Social Transformation for Military Service Members - Vaudreuil, Rebecca; Bronson, Hannah; Bradt, Joke (Frontiers in Psychology, 2019)
The use of music performance in music therapy with military service members is discussed as a vehicle for social transformation and reintegration. The use of performance in music therapy is not without controversy. Therapy is considered a process, not a product, and confidentiality and privacy are essential components of therapy. However, others have argued that public performances can validate therapeutic changes in clients, give voice to their experiences, raise awareness of social issues within their communities, transform perceptions of injury or illness in audience members, and may result in the clients gaining support and validation from their communities. We discuss the potential of music performances to contribute to individual development, reinforce rehabilitation, enhance function, and facilitate change at the community level to support reintegration of military service members. We illustrate this through two brief case reports of service members who received music therapy as part of their treatment for post-traumatic stress disorder, traumatic brain injury, and other psychological health concerns at the National Intrepid Center of Excellence, a Directorate of the Walter Reed National Military Medical Center, Bethesda, MD, USA. The service members wrote, learned, and refined songs over multiple music therapy sessions and created song introductions to share with audiences the meanings and benefits gained from integrating performance in music therapy. The case reports also include excerpts of interviews conducted with these service members several months after treatment about their experiences of performing and the perceived impact of their performances on the audience and greater community.